Enhancing photocatalytic degradation of quinoline by ZnO:TiO2 mixed oxide: Optimization of operating parameters and mechanistic study. (15th March 2020) - Gupta, Divya; Chauhan, Rohit; Kumar, Navneet; Singh, Vikash; Srivastava, Vimal Chandra; Mohanty, Paritosh; Mandal, Tapas Kumar
Abstract: This study focuses on the photocatalytic degradation of quinoline, a recalcitrant heterocyclic nitrogenous aromatic organic compound, using the mixed oxide ZnO–TiO2 photo-catalyst. Photo-catalysts were synthesized by the solid-state reaction method at different calcination temperatures of 400 °C, 600 °C, and 800 °C. Different analytical methods, including Field emission scanning electron microscope, Brunauer-Emmett-Teller surface area, X-ray diffraction, UV–vis diffuse reflectance spectroscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy analysis were used for the catalyst characterization. The highest pore surface area of 57.9 m 2 g −1 was obtained for the photo-catalyst calcined at 400 °C. The effects of calcination temperature, solution pH, initial concentration, catalyst dose as well as irradiation time were studied. At the optimum condition, i.e., calcination temperature of 400 °C, pH ≈8 and catalyst dose of 2.5 gL −1, maximum quinoline degradation and total organic carbon (TOC) removal efficiency of ≈92% and ≈78% were obtained after 240 min for initial quinoline amount of 50 mgL −1 . The 1 st, 2 nd, and n th -order kinetic models were applied to analyze the quinoline degradation rate. The photocatalytic mechanism was studied by drawing energy level diagram with the help of the band-gap structures of the ZnO and TiO2, potential of the free radicals like OH and O2 and HOMO-LUMO energy gap of the quinoline molecule. The proposed pathways of quinoline mineralization were suggested on the basis of the identified intermediates by the gas chromatograph-mass spectrometer analysis and scavenger study. Graphical abstract: Image 1 Highlights: Preparation of mixed oxide nano-photocatalyst ZnO–TiO2 having different molar ratio. Solid state reaction method used for catalyst preparation. Catalysts used for photo-catalytic quinoline degradation. Study of the effects of ZnO:TiO2 ratio, pH, initial concentration and catalyst dose.